Dynamic Membrane Filtration: Formation, Filtration, Cleaning, and Applications. Issue 1 (28th September 2017) - Li, Lucheng; Xu, Guoren; Yu, Huarong
Abstract: Applications of dynamic membrane (DM) filtration and factors affecting formation, filtration, and cleaning are introduced. DMs have been studied extensively for wastewater treatment in recent years. DM formation methods and mechanisms are explained. Effects of supporting material, deposited material, formation pressure, and pH on the DM formation are discussed in detail. The impacts of operation pressure, aeration intensity, cross‐flow velocity, temperature, and other parameters on the DM filtration process are evaluated and different DM cleaning strategies are reviewed. The applications of DMs to treatments of municipal wastewater, surface water, oily water, industrial wastewater, sludge, and microalgae harvesting are discussed. Finally, possible future research directions and some guidelines for DM technology are given. Abstract : High flux, low cost, and low operation pressure are the main advantages of dynamic membranes over traditional membrane technology in wastewater treatment. Different formation and filtration conditions as well as cleaning strategies for dynamic membranes are investigated. An overview of dynamic membrane applications in wastewater and sludge treatment is presented.